Cognitive and Physiologic Reserve Independently Relate to Superior Neurocognitive Abilities in Adults Aging With HIV. (1st August 2022) - Saloner, Rowan; Lobo, Judith D.; Paolillo, Emily W.; Campbell, Laura M.; Letendre, Scott L.; Cherner, Mariana; Grant, Igor; Heaton, Robert K.; Ellis, Ronald J.; Moore, David J.; ,
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: To investigate joint contributions of cognitive and physiologic reserve to neurocognitive SuperAging in older persons with HIV (PWH). Methods: Participants included 396 older PWH (age range: 50–69 years) who completed cross-sectional neuropsychological and neuromedical evaluations. Using published criteria, participants exhibiting global neurocognition within normative expectations of healthy 25-year-olds were classified as SuperAgers (SA; n = 57). Cognitively normal (CN; n = 172) and impaired (n = 167) participants were classified with chronological age-based norms. Cognitive reserve was operationalized with an estimate of premorbid verbal intelligence, and physiologic reserve was operationalized with a cumulative index of 39 general and HIV-specific health variables. Analysis of variance with confirmatory multinomial logistic regression examined linear and quadratic effects of cognitive and physiologic reserve on SA status, adjusting for chronological age, depression, and race/ethnicity. Results: Univariably, SA exhibited significantly higher cognitive and physiologic reserve compared with CN and cognitively impaired ( d s ≥ 0.38, p s < 0.05). Both reserve factors independently predicted SA status in multinomial logistic regression; higher physiologic reserve predicted linear increases in odds of SA, and higher cognitive reserve predicted a quadratic "J-shaped" change in odds of SA compared with CN (ie, odds of SA > CN only above 35th percentile of cognitive reserve). Conclusions: Each reserve factor uniquely related to SA status, which supports the construct validity of our SA criteria and suggests cognitive and physiologic reserve reflect nonoverlapping pathways of neuroprotection in HIV. Incorporation of proxy markers of reserve in clinical practice may improve characterization of age-related cognitive risk and resilience among older PWH, even among PWH without overt neurocognitive impairment.